PENGARUH MODEL PROJECT BASED LEARNING TERINTEGRASI KEARIFAN LOKAL DAN KEPERCAYAAN DIRI TERHADAP HASIL BELAJAR SISWA MENYAJIKAN DRAMA - Jumriah, Jumriah; Susilo, Susilo; Nina Queena HP (Journal of Innovation Research and Knowledge, 2025)
This research is motivated by the idea of ​​the importance of preserving local wisdom as an identity and character from various aspects of life, on the other hand the problem of low student self-confidence has become a problem, therefore, to accommodate this thought a learning model based on local wisdom is needed, innovation of implementing a project-based learning model integrated with local wisdom is expected to be able to answer the problem of student confidence and learning outcomes. The research was conducted at SMP Negeri 2 Bontang City (Junior High School 2 bontang city), as a representation of the largest junior high school in South Bontang District, Bontang City. The objectives were to determine: 1) the effect of learning using the project based learning (PjBL) model integrated with local wisdom on learning outcomes, 2) the effect of learning using the project based learning (PjBL) model integrated with local wisdom on self-confidence, 3) the interaction of using the project based learning (PjBL) model integrated with local wisdom and self-confidence on learning outcomes. The experimental research design used was “Pretest-Postest Non Equivalent Control Group Design, using a factorial research design of 2 x 4. Data were taken from 64 respondents of class VIII E and VIII F who were the research samples, through distributing self-confidence questionnaires and testing learning outcomes through pre and post tests. Data were analyzed using descriptive statistical analysis tools and two-way ANOVA inferential. The results of the study showed: 1) there is a significant influence of learning using the project based learning (PjBL) model integrated with local wisdom on learning outcomes (0.000 <0.05), or the F count value is greater than the F table value (88.434> 3.968), 2) there is an influence of learning using the project based learning (PjBL) model integrated with local wisdom on learning motivation (0.002<0.05), or the F count value is greater than the F table value (9.946> 3.968) 3) there is an interaction between the use of the project based learning (PjBL) model integrated with local wisdom and learning motivation on learning outcomes with a significance value (0.000<0.05), or the F count value is greater than the F table value (26.191>3.968)